Michel Leiris : writing the self - Hand, Seán (Cambridge studies in French, 2002)
This is the first full-length study in English of Michel Leiris's work. Frequently cited as a central figure in contemporary French culture, Seán Hand explores Leiris's participation in some of the most striking intellectual and artistic movements of the twentieth century; surrealism, ethnography and existentialism amongst others.